Swearing Words on YouTube Comment Column in CNN Political News - Febby Halimah Lubis (ELITE Association Indonesia, 2021)
This study aims to identify the types of swearing word and the reasons of swearing word that are used on YouTube comment column. This study conducts a descriptive qualitative research. The source of the data is taken from comment column of video uploaded by CNN about political news on YouTube. In analyzing the data, the researcher employs the theory proposed by Lakoff (1975) in order to identify the types of swearing word and the theory of Andersson (in Karjalainen, 2002:23) in order to describe the reasons of swearing word. The result of this study reveals that there are 17 data of swearing words, categorized into two types of swearing word, which are strong and weak swearing word and three reasons of swearing word, which are psychological, social and linguistic motive. The most dominant type is strong swearing word and the most dominant reason of using swearing word is psychological motive. The word fuck as the powerful taboo word is the most dominant word contained in the expressions of swearing word.